Sustaining yield and nutritional quality of peanuts in harsh environments: Physiological and molecular basis of drought and heat stress tolerance - Puppala, Naveen; Nayak, Spurthi N.; Sanz-Saez, Alvaro; Chen, Charles; Devi, Mura Jyostna; Nivedita, Nivedita; Bao, Yin; He, Guohao; Traore, Sy M.; Wright, David A.; Pandey, Manish K.; Sharma, Vinay (Frontiers in Genetics, 2023)
Climate change is significantly impacting agricultural production worldwide. Peanuts provide food and nutritional security to millions of people across the globe because of its high nutritive values. Drought and heat stress alone or in combination cause substantial yield losses to peanut production. The stress, in addition, adversely impact nutritional quality. Peanuts exposed to drought stress at reproductive stage are prone to aflatoxin contamination, which imposes restriction on use of peanuts as health food and also adversely impact peanut trade. Limited proress has been achieved to enhance abiotic stress adaptation in peanut through conventional breeding. A comprehensive understanding of the impact of drought and heat stress at physiological and molecular levels may accelerate the development of stress tolerant productive peanut cultivars adapted to a given production system. Significant progress has been achieved towards characterization of germplasm for drought and heat stress tolerance, unlocking the physiological and molecular basis of stress tolerance, identifying significant marker-trait associations as well major QTLs and candidate genes associated with drought tolerance, which after validation may be deployed to initiate marker-assisted breeding for adaptation of peanuts in drought stressed environments. The proof of concept about the use of transgenic technology to add value to peanuts has been demonstrated. Advances in phenomics and artificial intelligenes to accelerate timely and cost-effective collection of phenotyping data in large germplasm/breeding populations has also been discussed. Greater focuss is needed to accelerate research on heat stress tolerance in peanut. A suits of technological innovations are now available in the breeders toolbox to enhance productivity and nutritional quality of peanuts in harsh environments. A holistic breeding approach to simultaneously addressing both stresses could be a successful strategy to produce climate-resilient peanut germplasm with improved nutritional quality for use in peanut breeding